P6.068 Effect of an HIV Prevention Program Among Female Sex Workers on the Decline in Syphilis Prevalence Among Their Clients in South India. (13th July 2013) - Rajaram, S; Alary, M; Banandur, P; Thammattoor, U K; Thomas, T; Mainkar, M K; Paranjape, R; Adhikary, R; Duchesne, T; Isac, S
Abstract : Objective: As a part of evaluating the Avahan Programme, two rounds of integrated biological and behavioural assessment (IBBA) surveys were conducted in 2006–07 and 2009–10 among clients of female sex workers (FSWs) across 17 districts in south India to measure the prevalence of HIV and STIs, and related risk factors (n∼7, 000 per round). We examined the association between changes in programme indicators and changes in syphilis prevalence. Methods: Using a random-effect multilevel logistic regression, we examined the effect of district-specific programme indicators for FSWs (from the Avahan computerised monitoring system) on the decline in syphilis prevalence among clients of FSWs after controlling for significant individual level variables. Program indicators included their 2006 value, the difference in their values between the surveys, and the interaction between the latter and study round. The model also controlled for baseline syphilis prevalence and its interaction with survey rounds. Results: Syphilis prevalence among clients of FSWs decreased from 4.8% (round 1) to 2.6% (round 2; p < 0.001). The odds ratio (OR) of the interaction term between the difference in programme coverage (% of FSWs covered by the programme in a given year) and the round was 0.983 (p = 0.001), indicating that increase in coverage was significantly associated with the decrease in syphilis prevalence between rounds. ORs comparing syphilis prevalence between rounds varied with the level of increase in coverage and were statistically significant with coverage increase ≥ quartile (Q) 1: OR = 0.61 at Q1, 0.53 at Q2, 0.40 at Q3 and 0.13 at Q4. Conclusions: The results support that the Avahan intervention among FSWs had a significant impact in reducing syphilis prevalence among their clients in settings covered by the intervention. The triangulation of our results with those obtained among FSWs suggests a major impact of this intervention on the HIV/STI epidemic in southern India.